Measuring Unfair Inequality: Reconciling Equality of Opportunity and Freedom from Poverty - Hufe, Paul; Kanbur, Ravi; Peichl, Andreas (Review of Economic Studies, 2022)
Empirical evidence on distributional preferences shows that people do not judge inequality as problematic per se but that they take into account the fairness or unfairness of the outcome. This article conceptualizes a view of unfair inequality and introduces a new measure of inequality based on two widely held fairness principles: equality of opportunity and freedom from poverty. It develops a method for decomposing inequality and its trends into an unfair and a fair component. We provide two empirical applications of our measure. First, we analyse the development of inequality in the US from 1969 to 2014 from a fairness perspective. Second, we conduct a corresponding international comparison between the US and 31 European countries in 2010. Our results document that unfair inequality matches the well-documented inequality growth in the US since 1980. This trend is driven by decreases in social mobility, i.e., increasing importance of parental education and occupation for the income of their children. Among the 32 countries of our international comparison, the land of opportunity ranks among the most unfair societies in 2010.